Nondipping pattern on 24-h ambulatory blood pressure monitoring is associated with left ventricular hypertrophy in chronic kidney disease. Issue 5 (October 2018) - Jaques, David A.; Müller, Hajo; Martinez, Chantal; De Seigneux, Sophie; Martin, Pierre-Yves; Ponte, Belen; Saudan, Patrick
Abstract : Background: Few studies have assessed the role of 24-h ambulatory blood pressure monitoring (ABPM) in adults with nondialysis chronic kidney disease (CKD). We examined the potential determinants of left ventricular hypertrophy (LVH) and mass index (LVMI) in this population. Participants and methods: We carried out a cross-sectional study on 69 stage 3b-5 CKD adults who had ABPM and transthoracic echocardiography performed simultaneously. Hypertension (HT) was defined as 24 h blood pressure (BP) of at least 130/80 mmHg. ABPM parameters considered were BP dipping status, BP load, and the BP night-time/daytime ratio. We performed stepwise backward multivariate linear and logistic regression to assess the determinants of LVH and LVMI. ABPM parameters were considered the main independent variables, whereas HT, angiotensin-converting enzyme inhibitor/angiotensin II receptor antagonist use, glomerular filtration rate of less than 30 ml/min/1.72 m 2, diabetes, smoking, age, sex, hemoglobin, and parathyroid hormone levels were considered covariates. Results: LVH was present in 22 (31.8%) patients. In linear regression analysis, systolic [ β =−13.8, 95% confidence interval (CI)=−26.3 to −1.3, P =0.031] and mean ( β =−13.5, 95% CI=−25.7 to −1.2, P =0.031) nondipping status was associated with increased LVMI. BP load and night-time/daytime ABPM ratio were not associated with LVMI. In logistic regression analysis, systolic nondipping status (odds ratio=0.27, 95% CI=0.08–0.91, P =0.036) was associated with LVH. Among covariates, estimated glomerular filtration rate of less than 30 ml/min/1.72 m 2 and HT were associated with LVH and increased LVMI. At 1-year follow-up, mean nondipping status on the initial ABPM remained associated significantly with increased LVMI ( β =−19.8, 95% CI=−36.6 to −3.0, P =0.022). Conclusion: These data confirm the high incidence of LVH among nonrenal replacement therapy CKD patients and suggest that the nondipping phenomenon on ABPM is associated independently with LVH and increased LVMI in this population. Abstract : Supplemental Digital Content is available in the text.